Health Care Utilization Among Homeless Veterans in Chicago. Issue 3 (12th November 2019) - Raad, Jason H; Tarlov, Elizabeth; Kho, Abel N; French, Dustin D
Abstract: Introduction: The U.S. Department of Veterans Affairs (VA), the single largest health care system in the United States, provides comprehensive medical and behavioral health services to more than 9 million Veterans. The size and scope of the VA's system of care allow health care providers, policymakers, and community stakeholders to conduct detailed analyses of health care utilization among Veterans; however, these analyses do not include health care encounters that occur outside VA. Although many Veterans obtain care in non-VA settings, understanding health care utilization among vulnerable populations of Veterans, including those who are homeless or at risk of becoming homeless, is needed to identify potential opportunities to enhance access and reduce fragmentation of care. Materials and Methods: VA administrative data were merged with data from the Chicago HealthLNK Data Repository to identify Veterans eligible for VA services who were homeless, or at risk of becoming homeless, in the greater Chicago metropolitan area for the years 2010–2012. Results: During the 3-year study period, about 208, 554 Veterans were registered for care at two VA medical centers located in the City of Chicago and an adjacent suburb. Of those, 13, 948 were identified as homeless or at risk of becoming homeless. Results suggest that 17% ( n  = 2, 309) of Veterans in this sample received some or all of their care in the community. Much of the care these Veterans received was for chronic health conditions, substance use, and mental health disorders. Conclusions: Veterans eligible for VA servicers who are homeless, or at risk of becoming homeless, frequently sought care in the community for a variety of chronic health conditions. Health information exchanges and partner-based registries may represent an important tool for identifying vulnerable Veteran populations while reducing duplication of care.